Climate and stock influences on the spread and locations of catches in the northeast Atlantic mackerel fishery. (28th October 2015) - Hughes, K.M.; Dransfeld, L.; Johnson, M.P.
Abstract: The poleward movements of northeast Atlantic (NEA) mackerel ( Scomber scombrus ) catches, possibly linked to climate change, are causing a major international disagreement over quotas. We present an analysis of spatially resolved catch data from 1977 to 2013 that shows how a northward shift is only part of the change in the fishery. There was a 30‐yr trend for declining catches per ICES rectangle (0.5° latitude by 1°‐degree longitude) until 2011–2013. Catches also moved further offshore, to areas of deeper waters. Segmented regressions suggested discontinuities in the temporal pattern of change in catch‐related variables. In particular, the number of ICES rectangles fished rose sharply around 1987. Generalized additive models (GAMs) suggest that much of the movement of fishing activity to areas of deeper water can be associated with variation in the Atlantic Multidecadal Oscillation (AMO) and the North Atlantic Oscillation (NAO). GAM models had a lower predictive error than linear or simple autoregressive models of change in catch‐related variables. Although climate indices can be linked to some of the changes in catch, it may be difficult to extrapolate future patterns in the catch: some of the GAM smoothers are non‐linear, and the oceanographic processes linked to climate index values are not homogenous across the area occupied by mackerel. A practical implication of the reported changes in catch since 1977 is that vessels are now reportedly fishing further offshore, which has implications for fuel consumption and profitability of the fishery.